Subsistence and Development - Umari, N. (Journal of Income Distribution®, 1993)
The paper takes the theory of social organization of the fourteenth century historian Ibn Khaldun as the reference point for discussion of premodern economy. It is argued that the subsistence sector in W.A. Lewis’s theory of development deviates in critical respects from premodern forms. The subsistence sector has undergone an unspecified transformation that enables it to meet the requirements of growth in the capitalist sector. The nation-state provides the background institutions to bind the subsistence and modern sectors into a single economy.